All‐Solid‐State Garnet‐Based Lithium Batteries at Work–In Operando TEM Investigations of Delithiation/Lithiation Process and Capacity Degradation Mechanism (Adv. Sci. 5/2023). Issue 5 (14th February 2023) - Hou, An‐Yuan; Huang, Chih‐Yang; Tsai, Chih‐Long; Huang, Chun‐Wei; Schierholz, Roland; Lo, Hung‐Yang; Tempel, Hermann; Kungl, Hans; Eichel, Rüdiger‐A.; Chang, Jeng‐Kuei; Wu, Wen‐Wei
Abstract : All‐Solid‐State Li Batteries In article number 2205012, Rüdiger‐A. Eichel, Wen‐Wei Wu, and co‐workers successfully investigated the dynamic delithiation/lithiation process of LCO/LLZO solid‐state Li battery (SSLB) by in operando TEM. In stable potential charging, the d‐spacing of LCO was increased during delithiation process because of columbic repulsion caused by Li vacancy. In contrast, d‐spacing was decrease since Li ions return the original sites. Additionally, after multiple cycling process, the interface delamination and crack occurred in LCO. Furthermore, metallic Co precipitated in LCO grain in over‐charging potential. The work gives constructive information which can optimize the fabrication of SSLB.